2000
DOI: 10.1523/jneurosci.20-12-04708.2000
|View full text |Cite
|
Sign up to set email alerts
|

Modeling LGN Responses during Free-Viewing: A Possible Role of Microscopic Eye Movements in the Refinement of Cortical Orientation Selectivity

Abstract: Neural activity appears to be essential for the normal development of the orientation-selective responses of cortical cells. It has been proposed that the correlated activity of LGN cells is a crucial component for shaping the receptive fields of cortical simple cells into adjacent, oriented subregions alternately receiving ON- and OFF-center excitatory geniculate inputs. After eye opening, the spatiotemporal structure of neural activity in the early stages of the visual pathway depends not only on the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 99 publications
(116 reference statements)
4
30
0
Order By: Relevance
“…Estimating correlated activity Although rectification is a critical component of geniculate responses, previous simulations in which the rectification threshold of geniculate cells was systematically varied to eliminate up to 50% of the dynamic range of responses have shown a modest influence of the level of rectification on the patterns of correlated activity (Rucci et al, 2000). For this reason, in this study we neglected the rectification operated by geniculate units.…”
Section: Nne-11mentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating correlated activity Although rectification is a critical component of geniculate responses, previous simulations in which the rectification threshold of geniculate cells was systematically varied to eliminate up to 50% of the dynamic range of responses have shown a modest influence of the level of rectification on the patterns of correlated activity (Rucci et al, 2000). For this reason, in this study we neglected the rectification operated by geniculate units.…”
Section: Nne-11mentioning
confidence: 99%
“…al., 2003). Furthermore, modeling studies that simulated neural responses during free-viewing suggest that fixational instability profoundly affects the statistics of thalamic (Rucci et al, 2000) and thalamocortical activity (Rucci and Casile, 2004;Parsons and Rucci, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…After eye opening, small eye and body movements keep the retinal image in constant motion. The statbtical analysis of thio paper, together with the results of our previous simulations (Rucci et aL, 2000;Rucci & Casile, 2004), indicate that the phyoiological inotability of visual fixation eontributes to decorrelating cell responses to natural stimuli and establishing a regime of neural activity similar to that present before eye opening. Thus 1 at the time of eye opening 1 no sudden change occurs in the second-order statistics of thalamocortical aetivity 1 and the same correlation-based mechanism of synaptic plasticity can account for both the initial emergenee and the later refinement of simple cell receptive fields.…”
Section: Xj Xo)) (I: H"(t)tlt I: Hry(t)th)mentioning
confidence: 59%
“…Results from previous computational studies have shown a strong inHuence of fixational instability on the structure of correlated activity in models of the LGN and Vl (Rucci et al, 2000;Rucci & Casile, 2004). To examine the origins of this influence, in this paper we modeled fixational instability by means of a two-dimensional ergodic: process t;(t.) = [Ex(t), ~y(t)]T For simplicity, we assumed zero moments of the firstorder ( (~x(t)) = 0 and (~y(t)) = 0) and uncorrele1ted movements along the two axes (R(,,(,(t) = 0).…”
Section: Introductionmentioning
confidence: 99%